Pre- and peri-operative factors influence autogenous tooth transplantation healing in insufficient bone sites - Thanapon Suwanapong; Aurasa Waikakul; Kiatanant Boonsiriseth; Nisarat Ruangsawasdi (BMC, 2021)
Abstract Background The amount of bone remaining at the transplant site for autogenous tooth transplantation can facilitate successful healing. Therefore, this retrospective study evaluated the factors influencing the healing of 50 successful autogenous tooth transplantations with insufficient bone support at the transplanted site without a bone graft. Methods The factors were classified as pre- and peri-operative factors, and the healing outcomes were clinical and radiographic observations. The factors were statistically analyzed using the chi-square test to identify correlations between the pre- and peri-operative factors and the clinical and radiographic outcomes. The T-test or one-way analysis of variance was used to compare the percent bone change in each factor. Results The results indicated that gingival healing was delayed in the intra-arch transplantations, and pulp obliteration was seen earlier when transplanted in the maxilla. Patients under 18-years-old demonstrated a greater percent bone change than the over 18-year-old patients, while the peri-operative variables did not have a relationship with clinical healing and the amount of bone change over 12 months. Furthermore, the percent bone change significantly increased during the first three months. Conclusions In conclusion, pre-operative factors, age and transplant site, influenced the healing rate of autogenous transplanted teeth. In contrast, the peri-operative factors were not related with the clinical and radiographic outcomes. Generating the least trauma to the periodontal ligament cells is the most important concern.